ANALISIS YURIDIS TERHADAP PUTUSAN HAKIM YANG MENGABULKAN EKSEPSI TERGUGAT (STUDI KASUS PUTUSAN NO. 74/PDT.G/2021/PN.BKS) - Biyanda Rizky; Muriani Muriani (Reformasi Hukum Trisakti, 2021)
The people who suffered losses as a result of the evictions carried out by the Bekasi City Government filed a lawsuit with the District Court. Bekasi with the argument that the Municipal Government of Bekasi has committed an unlawful act (PMH). However, in the trial of the Panel of Judges PN. Bekasi grants the Defendant's exception regarding the Absolute Authority of the Court, taking into account PERMA No. 2/2019 which resulted in this case ending before entering the process of examining the main case. The formulation of the problem is: is the consideration of the judge who granted the exception in accordance with the statutory regulations? And what legal remedies can be made against this decision? The normative research method, with reference to secondary data, namely library materials, while to analyze the data is done qualitatively, and conclusions are made deductively. Research results, discussion and conclusions: Panel of Judges PN. Bekasi, which granted the defendant's exception, was not careful in looking at the nature of the lawsuit and ignored SEMA No. 2/2019, against the final decision stating that the District Court is not authorized to examine and adjudicate, an appeal can be made to the High Court.